Kemampuan penalaran matematis mahasiswa berdasarkan variasi gender dan self-efficacy matematis - Samsul Bahri; Farah Heniati Santosa; Kiki Riska Ayu Kurniawati; Habibi Ratu Perwira Negara (Mahesa Research Center, 2021)
The purpose of this study was to determine the differences in mathematical reasoning ability (KPM) based on gender variation (VG) and mathematical self-efficacy (SEM). Quantitative research was chosen to answer the research question. The research design used comparative causality on 75 students at a State University in Mataram City. Data collection was based on gender variance in the selected sample (51 women and 24 men, KPM test scores consisting of 5 items, and a 20-point SEM questionnaire, which were further categorized into 3 levels (low, medium and high). Analysis The data used two-way ANOVA with a 3 x 2 factorial design. The post-anava follow-up test used the turkey test. The results showed that male KPM was better than female KPM. Based on SEM category, student KPM at high SEM was better than student KPM at low SEM This finding emphasizes the importance of instructors being able to observe the characteristics of self-efficacy and gender variations that have an impact on the mathematics learning process.